Characterization of SiO2/Ag composite particles synthesized by in situ reduction and its application in electrically conductive adhesives. (15th October 2015) - Xu, Chao; Li, Wen-jun; Wei, Ying-min; Cui, Xiao-ying
Graphical abstract: Highlights: SiO2 /Ag composite particles were prepared via a novel and facile approach. The silver shell thickness of SiO2 /Ag particles was controlled by the reaction conditions. SiO2 /Ag particles had core–shell morphology and the silver nanoparticles had FCC structure. The synthetic mechanism of SiO2 /Ag composite particles was discussed. Small content SiO2 /Ag improved the electrical bulk resistivity and tensile shear strength. Abstract: In the study, SiO2 /Ag composite particles with silver coating onto the surface of silica have been successfully prepared via a novel and facile approach (Oxidation–Reduction Method). In this approach, the SiO2 particles were first modified with 3-ammoniatriethoxysilane (APTES) and glyoxalic acid (GA) through two-step reaction, the aldehyde group (CHO) were anchored onto the surfaces of silica spheres via electrostatic attraction, these [Ag(TEA)2 ] + ions in the solution were then reduced by the CHO and coated onto the surface of silica to obtain SiO2 /Ag composite particles. The effects of the reaction conditions on silver content and synthetic mechanism had also been discussed. The structure, morphology and optical properties of the SiO2 /Ag composite particles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV–vis spectroscopy. The results showed the surface of SiO2 was surrounded by pure silver nanoparticles, and the silver nanoparticles had face-centered-cubic structure, the SiO2 /Ag composite particles with core–shell morphology and special optical properties. And the small content SiO2 /Ag composite particles applied in electrically conductive adhesives (ECAs) improved the electrical bulk resistivity and tensile shear strength.